Treatment patterns of glioma in Pakistan: An epidemiological perspective - Mohammad Hamza Bajwa; Muhammad Usman Khalid; Mashal Murad Shah; Muhammad Shahzad Shamim; Altaf Ali Laghari; Naveed Zaman Akhunzada; Saad bin Anis; Muhammad Faraz Raghib; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To define the landscape of treatment patterns and current epidemiological data regarding gliomas in Pakistan. Methods: As part of the Pakistan Brain Tumour Epidemiology Study (PBTES), data were collected from 32 neurosurgical centres across the country. Our retrospective study looked at patients who underwent surgical procedures for gliomas in 2019 in neurosurgical centres. The data was collated and analysed using STATA version 15. Results: A total of 781 patients with gliomas were identified 479(61.8%) in public sector hospitals, 302(39.1%) in the private sector). The most common histopathological subtypes were glioblastoma 262 (33.5%), followed by astrocytoma 147(18.8%) and oligodendroglioma 93(11.9%). Gender distribution was skewed towards men 508(65%). Private institution hospitals performed surgical biopsies as the first surgical procedure 75(23%) more often than public hospitals 38(9%). Chemotherapy was given to 115(29.8%) patients, and there was no data regarding 467(53%) of patients. Similarly, only 202(43.9%) patients received radiation therapy, and there was no data for 469(60%) of patients. For high-grade gliomas specifically, only 95(31.8%) patients with HGG have a record of receiving radiation therapy, and only 57(18.9%) had a record of being started on chemotherapy. Conclusions: Our study highlighted gaps in glioma management within Pakistan, with only around half of our patients receiving chemotherapy and radiotherapy, despite it being indicated. In our experience, high-grade tumours were diagnosed at a younger age than in high-income countries, but overall, glioblastoma was a smaller constituent of our tumour sample than expected. Keywords: Glioblastoma. Oligodendroglioma, Glioma, Astrocytoma, Brain Neoplasms, Registries, Epidemiology. Continue...